On the issue of pregnancy management in monochorionic twins - V. I. Tsibizova; D. O. Saprykina; T. M. Pervunina; V. O. Bitsadze; N. A. Makatsariya; D. V. Blinov; G. C. Di Renzo (Акушерство, гинекология и репродукция, 2022)
Nowadays, the management and delivery of multiple pregnancies in the era of increased rate of multiple pregnancies is essential in work of an obstetrician-gynecologist. However, it is an ultrasound scanning that becomes a starting point to choose management strategies for multiple pregnancies. Despite tremendous advances in understanding the pathogenesis of developing specific complications, multiple pregnancies still account for a large proportion of perinatal complications. Therefore, continuously improving knowledge in antenatal diagnostics, the principles of prenatal care and optimal approach to delivery is fundamental for reducing morbidity and mortality rate related to multiple pregnancies.